Reconstruction Old Students Image Using The Autoencoder Method - Negara, Candra Putra; Zaman, Azmi Badhi’uz; Setiawan, Dimas Aji; Azhari, Ahmad (Universitas Negeri Malang, 2022)
Image Processing is image processing with a digital computer to produce new images according to the user's wishes. One implementation is to reconstruct the image. Through the extraction stages are able to get the characteristics of an image. The algorithm used is Adam Optimization, which is an extension of the stochastic gradient reduction that has just seen wider adoption for deep learning applications in computer vision and natural language processing. In this study using the autoencoder technique, which is one variant of artificial neural networks that are generally used to